Pengaruh Persepsi Harga, Varian, dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Xiaomi - Odrick Helsar L. Tobing; Budi Setiawan (Jurnal Ilmiah Manajemen Kesatuan, 2020)
This study aims to see if Perception Of Price, Variance and Products, and Quality Of Products affect bot partial and simultaneous Decision Of Purchase. The population in this study was a student of IBIK Bogor who once use Xiaomi’s Smartphone in IBIK Bogor with 100 samples. The Slovin method used a is a non-sampling method with an approximate sampling type. The result of this study are as follows: (1) a Partial Value perceotions affect the decision of the purchase with a higher value T count than T table(3.316> 1.94). (2) a partial Product Variant affects the decision of the purchase with value of T greater than T table (3,461> 1.94). (3) The Quality of The Product is partial to the decision of the Purchase with a value of T count greater than T table (2.813> 1.94). (4) Perceptions Of Price, Variance Of Products, and Quality Of Products Simultaneously have positive and significant effects on purchasing decisions with greater F count than F table (65.297> 3.09) and significant value of 0.000. (5) The three independent variables (Value Perceptions, Product Variant, and Product Quality) are able to explain variations in dependencies (Purchasing Decision) of 67,3%, while 32,7% of purchasing decision are affected by other independent variables Keywords: perceived price, products’ varians, product quality, buying decision